Answer:
0=0
Step-by-step explanation:
(x+6)(x-5) = x^2 + - 30
Step 1: Simplify both sides of the equation.
x^2 + x-30 = x^2 + x-30
Step 2: Subtract x^2 from both sides.
x^2 + x - 30 - x^2 = x^2 + x - 30 - x^2
x-30=x-30
Step 3: Subtract x from both sides.
x-30-x=30-x
-30 = - 30
step 4: Add 30 to both sides.
-30+ 30 = -30 + 30
0=0
Given:

Solve:

Use l'hopital's rule:

Simplify:

Apply the constant multiple rule:


Similary :
The area of the square is calculated through the equation,
Area = e²
where e is the measure of sides.
From the given,
64 = e²
e = sqrt 64 = 8 inches
The length of the side of the square rotated to form the cylinder is the diameter of the base of the cylinder. To get the radius, we divide the diameter by 2.
radius = 8 inches / 2 = 4 inches
Thus, the radius of the cylinder is equal to <em>4 inches</em>.